ENHANCING CREATIVE COMMUNICATIVE COMPETENCE THROUGH PROBLEM –BASED TEACHING IN FOREIGN LANGUAGE EDUCATION (International conference on multidisciplinary science, 2025)
One of the most successful learner-centered technologies in contemporary pedagogy, especially in the area of foreign language instruction, is problem-based learning, or PBL. PBL, in contrast to conventional teacher-centered methods, promotes students to use inquiry, teamwork, and critical thinking to solve real-world issues. This essay examines how PBL promotes the growth of creative communicative competence, a critical 21st-century talent that blends language proficiency with inventiveness, intercultural awareness, and flexibility. According to the data, PBL encourages pupils to utilize language in real-world situations while also improving their accuracy and fluency. Furthermore, PBL combines speaking, listening, reading, and writing abilities into a unified communication process by involving students in problem-solving activities. The results imply that PBL offers a creative and long-lasting framework for language acquisition when accompanied by digital tools and reflective evaluation.